Teenagers perceptions of english learning in virtual settings - Banchón Cedeño, Elianie Yaritza (2023)
Due to the global health crisis caused by the COVID-19 pandemic, the educational system changed to virtual mode. This paper shows the results of a research conducted at Unidad Educativa 'Teodoro Wolf', on the perception of 7 students and 5 teachers. As a matter of fact, perception is a broad topic and essential for learning, understanding and perceiving our environment and context. Through online education we can make objects attractive so that they can and want to be perceived by learners. However, the truth is that they are not always taken into account. Therefore, the present research project was developed with the aim of investigating perceptions of English language learning in virtual environments. This academic work included as methodology the qualitative method, and also involved bibliographic research and phenomenological study. The sample stated that the instrument has a sufficient degree of reliability and accuracy. It was concluded that according to the results, the students received a solid vision of virtual education.